New tools for assessing information literacy: Knowing and doing - Nierenberg, Ellen; Låg, Torstein; Dahl, Tove I. (Septentrio Conference Series, 2021)
There is a need for short and easily administered measures for assessing students’ levels of information literacy (IL), as currently existing measures are long and cumbersome. We have therefore created a suite of tools, the “Tromsø Information Literacy Suite” (TROILS), for IL assessment. This suite of tools is freely available on an open platform for others to both use, adapt, and supplement. In this presentation, we introduce three TROILS assessment tools: 1.a test to assess students’ knowledge of key aspects of IL 2.a source evaluation measure to assess students’ abilities to select and critically evaluate sources 3.a source use measure to assess students’ abilities to use sources correctly when writing Together, these tools measure what students know and do regarding key facets of IL. We will discuss the tools’ development and present results of our research with students at different levels higher education.The IL test was developed using procedures intended to ensure acceptable psychometric measurement properties. These included expert consultation for content validity, student think-aloud-protocols for readability, item selection based on a pilot sample, exploratory factor analysis, and measures of reliability and validity. The test was deployed during the fall semester of 2019. In addition to assessing students’ IL levels, test results were used to explore the dimensionality of the IL construct. Results indicate that IL is a heterogeneous construct, and we will discuss important implications of this find for how IL is measured. Results from the source evaluation and source use measures were compared with test results to see whether what the students actually do in their coursework correlates with what they know, based on the test. Results indicate weak to moderate, but statistically significant, correlations. All three measures will be used longitudinally to measure students’ progress over three years.